2018
DOI: 10.1016/j.neuroimage.2018.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of global signal regression on characterizing dynamic functional connectivity and brain states

Abstract: Recently, resting-state functional magnetic resonance imaging (fMRI) studies have been extended to explore fluctuations in correlations over shorter timescales, referred to as dynamic functional connectivity (dFC). However, the impact of global signal regression (GSR) on dFC is not well established, despite the intensive investigations of the influence of GSR on static functional connectivity (sFC). This study aimed to examine the effect of GSR on the performance of the sliding-window correlation, a commonly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 69 publications
2
45
0
Order By: Relevance
“…The following sequence of steps was completed Turner, 1996) and signals from white matter and ventricles were regressed from the BOLD time courses for each gray matter voxel, to correct for head motion and physiological noise. Global signal regression was not applied, given that this procedure has been suggested to alter the covariance structure of the data (Murphy, Birn, Handwerker, Jones, & Bandettini, 2009), particularly when assessing dynamics (Xu et al, 2018). After smoothing, the voxel time courses were band-pass filtered (0.01-0.1 Hz) to alleviate low-frequency drifts and high-frequency physiological noise (Cordes et al, 2001).…”
Section: Image Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…The following sequence of steps was completed Turner, 1996) and signals from white matter and ventricles were regressed from the BOLD time courses for each gray matter voxel, to correct for head motion and physiological noise. Global signal regression was not applied, given that this procedure has been suggested to alter the covariance structure of the data (Murphy, Birn, Handwerker, Jones, & Bandettini, 2009), particularly when assessing dynamics (Xu et al, 2018). After smoothing, the voxel time courses were band-pass filtered (0.01-0.1 Hz) to alleviate low-frequency drifts and high-frequency physiological noise (Cordes et al, 2001).…”
Section: Image Preprocessingmentioning
confidence: 99%
“…After smoothing, the voxel time courses were band-pass filtered (0.01-0.1 Hz) to alleviate low-frequency drifts and high-frequency physiological noise (Cordes et al, 2001). Global signal regression was not applied, given that this procedure has been suggested to alter the covariance structure of the data (Murphy, Birn, Handwerker, Jones, & Bandettini, 2009), particularly when assessing dynamics (Xu et al, 2018).…”
Section: Image Preprocessingmentioning
confidence: 99%
“…In support of this view, Nikolaou et al (2016) found that nuisance regression diminished but did not completely remove the relationship between network degree and measures of cardiac and respiratory activity. On the other hand, Xu et al (2018) reported that global signal regression (GSR) had a spatially heterogeneous impact 40 on DFC estimates, but did not assess whether GSR removed GS contributions from the DFC estimates.…”
Section: Introductionmentioning
confidence: 99%
“…The global rs-fMRI signal is a critical confound of correlation analysis with many contributing factors from both physiological and non-physiological sources. In particular, whether the global mean fMRI signal should be removed before the analysis, which can create spurious correlation features, has been debated [36][37][38][39][40][41][42]44 . Also, the global rs-fMRI signal can over-shadow specific intrinsic RSN features, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high variability in different dynamic states, physiological and non-physiological confounding factors also contribute to the rs-fMRI lowfrequency oscillation [33][34][35] . In particular, global fMRI signal fluctuations are one of the most controversial oscillatory features to be linked to dynamic brain signals [36][37][38][39][40][41][42][43][44] . For example, the rs-fMRI signal from the white-matter tract has been used as a nuisance regressor to remove the global noise contribution 45,46 .…”
Section: Introductionmentioning
confidence: 99%